The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0004-282x2012001000010
|View full text |Cite
|
Sign up to set email alerts
|

The expanded spectrum of neuromyelitis optica: evidences for a new definition

Abstract: Neuromyelitis optica (NMO) has been traditionally described as the association of recurrent or bilateral optic neuritis and longitudinally extensive transverse myelitis (LETM). Identification of aquaporin-4 antibody (AQP4-IgG) has deeply changed the concept of NMO. A spectrum of NMO disorders (NMOSD) has been formulated comprising conditions which include both AQP4-IgG seropositivity and one of the index events of the disease (recurrent or bilateral optic neuritis and LETM). Most NMO patients harbor asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
2
26
0
5
Order By: Relevance
“…1: Lesions present in up to 60% of patients [9]; 2: Lesions located periventricular zone and brainstem a (involving more frequently its central and dorsal aspects [28]). 3: Lesions localized at sites of high AQP4 expression such as in hypothalamus a [28] .…”
Section: Findings/diseasementioning
confidence: 99%
See 3 more Smart Citations
“…1: Lesions present in up to 60% of patients [9]; 2: Lesions located periventricular zone and brainstem a (involving more frequently its central and dorsal aspects [28]). 3: Lesions localized at sites of high AQP4 expression such as in hypothalamus a [28] .…”
Section: Findings/diseasementioning
confidence: 99%
“…3: Lesions localized at sites of high AQP4 expression such as in hypothalamus a [28] . 4: Corticospinal tract lesions frequently bilateral involving the posterior limb of the internal capsule and the cerebral peduncle a [28]. 5: Lesions lining the ependymal surface of the lateral ventricles a [28].…”
Section: Findings/diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the diagnosis of NMOSD is usually suspected in patients with the following phenotypes: monophasic or recurrent NMO, monophasic or recurrent longitudinally extensive transverse myelitis (LETM) that extends over three or more vertebral segments, and bilateral simultaneous or recurrent ON 6 . Although many patients have no lesions outside the optic nerve and spinal cord, several reports confirmed that NMOSD patients might also have some characteristic brain or brainstem lesions for NMO 7,8,9,10 , resulting in proposed diagnostic criteria that includes more features now considered typical for NMOSD 11 . Serum antibodies against aquaporin-4 (AQP4) are present in the majority of NMOSD patients and its discovery clearly segregated NMOSD from multiple sclerosis (MS) 12 .…”
mentioning
confidence: 99%